2004
DOI: 10.1038/sj.npp.1300555
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Hippocampal 5-HT2A Receptor Binding in Older Depressed Patients Using [18F]Altanserin Positron Emission Tomography

Abstract: Serotonin receptor changes have been associated with the pathophysiology and treatment of major depression. Only one other study has investigated serotonin receptor changes in older depressed patients. We used positron emission tomography (PET) and [ 18 F]altanserin, a ligand with high affinity for the 5-HT 2A receptor, to examine the relationship between 5-HT 2A receptor density and depression. Depressed subjects (n ¼ 16), age450 years, were recruited as part of a larger study. Older depressed subjects consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 39 publications
2
38
0
Order By: Relevance
“…For example, it has been shown that cortical 5-HT 2A receptor expression is increased in postmortem samples of depressed and suicidal patients (Mendelson, 2000;Pandey et al, 2002;Shelton et al, 2009), whereas 5-HT 2A binding was decreased in the hippocampus of depressed patients (Sheline et al, 2004). Furthermore, it has been shown that medication-free depressed patients with high pessimistic attitudes have increased 5-HT 2A receptor binding in the PFC compared with healthy control subjects (Meyer et al, 2003;Bhagwagar et al, 2006;Meyer, 2012).…”
Section: B Possible Use In Depressionmentioning
confidence: 99%
“…For example, it has been shown that cortical 5-HT 2A receptor expression is increased in postmortem samples of depressed and suicidal patients (Mendelson, 2000;Pandey et al, 2002;Shelton et al, 2009), whereas 5-HT 2A binding was decreased in the hippocampus of depressed patients (Sheline et al, 2004). Furthermore, it has been shown that medication-free depressed patients with high pessimistic attitudes have increased 5-HT 2A receptor binding in the PFC compared with healthy control subjects (Meyer et al, 2003;Bhagwagar et al, 2006;Meyer, 2012).…”
Section: B Possible Use In Depressionmentioning
confidence: 99%
“…Contradictory findings have been reported in the literature, with some studies reporting decreased GDNF levels (Straten et al, 2009;Otsuki et al, 2008), but others report increased GDNF levels in affective disorders (Barbosa et al, 2011;Rosa et al, 2006;Michel et al, 2008;Wang et al, 2011). Given that GDNF has an important role in the survival and maintenance of monoaminergic neurons, it is tempting to hypothesize that the reduction of GDNF levels may have a close relationship to the abnormal regulation of the serotoninergic system, as the significant reduction of post and pre-synaptic serotonin receptors observed in patients with late-life depression (Sheline et al, 2004;Meltzer et al, 2004). Such changes were correlated to the severity of depressive symptoms (Meltzer et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…10 Positron emission tomography (PET) with [ 11 C]DASB and [ 18 F]altanserin has widely been used to investigate the availability of serotonin transporter (SERT) and serotonin receptor 5-HT 2A in both humans and animals. [11][12][13][14] This imaging method has proven to be helpful in elucidating the role of serotoninergic mechanisms in aging, 15 and neurologic and psychiatric pathologies such as Alzheimer's disease, 16 depression 17,18 obsessive-compulsive disorder, 19 bipolar disorder, 20 and schizophrenia. 21 Nevertheless, the role of serotoninergic neurotransmission in stroke evolution using PET imaging has scarcely been explored to date.…”
Section: Introductionmentioning
confidence: 99%